Flat-detector computed tomography PBV map in the evaluation of presurgical embolization for hypervascular brain tumors. (17th November 2016) - Wen, Li-Li; Zhang, Xin; Zhang, Qing-Rong; Wu, Qi; Chen, Shu-Juan; Deng, Jin-Long; Huang, Kaiyi; Wang, Han-Dong
Abstract : Background: Preoperative embolization of hypervascular brain tumors is frequently used to minimize intraoperative bleeding. Objective: To explore the efficacy of embolization using flat-detector CT (FDCT) parenchymal blood volume (PBV) maps before and after the intervention. Materials and methods: Twenty-five patients with hypervascular brain tumors prospectively received pre- and postprocedural FDCT PBV scans using a biplane system under a protocol approved by the institutional research ethics committee. Semiquantitative analysis, based on region of interest measurements of the pre- and post-embolization PBV maps, operating time, and blood loss, was performed to assess the feasibility of PBV maps in detecting the perfusion deficit and to evaluate the efficacy of embolization. Results: Preoperative embolization was successful in 18 patients. The relative PBV decreased significantly from 3.98±1.41 before embolization to 2.10±2.00 after embolization. Seventeen patients underwent surgical removal of tumors 24 hours after embolization. The post-embolic tumor perfusion index correlated significantly with blood loss (ρ=0.55) and operating time (ρ=0.60). Conclusions: FDCT PBV mapping is a useful method for evaluating the perfusion of hypervascular brain tumors and the efficacy of embolization. It can be used as a supplement to CT perfusion, MRI, and DSA in the evaluation of tumor embolization.